Blue Economy of Bangladesh: Opportunities and Challenges for Sustainable Development - Islam, Md. Khairul; Rahaman, Mahbubur; Ahmed, Zobayer (Advances in Social Sciences Research Journal, 2018)
The blue economy refers to the economic activity based on maritime resources. The paper aims to explore the current scenario of sea resources of Bangladesh. Using secondary data, the study reveals that Bangladesh can accelerate its economic growth through the sustainable use of the sea resources. Moreover, Bangladesh has 710 km long coastline with 200 Nautical Miles of an exclusive economic zone inside the Bay of Bengal. Marine fisheries contribute 19.4% of the total fish production of the country. Besides, the western coastline of Cox’s Bazaar is the longest sea beach in the planet that is visited by on an average, 81% of the international tourists arrive in Bangladesh. However, due to lack of institutional capacity and given the socio-cultural context, the sustainability of the sea resources is now facing critical threats. Apart from studying the present status of sea resources, the paper proposed some way forwards based on existing opportunities and challenges for promoting sustainable development in Bangladesh.